2014
DOI: 10.1111/jdv.12667
|View full text |Cite
|
Sign up to set email alerts
|

New posology of potassium iodide for the treatment of cutaneous sporotrichosis: study of efficacy and safety in 102 patients

Abstract: Through statistical analysis, the usual posology was not shown to be superior to the one proposed in this study. Serology for sporotrichosis may be used as a valuable tool in the clinical monitoring of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 22 publications
(29 reference statements)
3
33
0
4
Order By: Relevance
“…The indiscriminate use of these antifungal drugs to treat classical and non-aggressive forms of sporotrichosis and other mycoses may have led to the emergence of resistance mechanisms. Sporotrichosis can be treated with non-antimycotic drugs such as potassium iodide (Bonifaz et al 2007, Macedo et al 2015) and with non-pharmacologic strategies such as hyperthermia (Bonifaz et al 2007) and cryosurgery (Almeida-Paes et al 2016), or even with a combination of low drug dosages and hyperthermia (Haruna et al 2006). The non-pharmacologic approaches are interesting because they often accelerate clinical cures, reducing treatment costs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The indiscriminate use of these antifungal drugs to treat classical and non-aggressive forms of sporotrichosis and other mycoses may have led to the emergence of resistance mechanisms. Sporotrichosis can be treated with non-antimycotic drugs such as potassium iodide (Bonifaz et al 2007, Macedo et al 2015) and with non-pharmacologic strategies such as hyperthermia (Bonifaz et al 2007) and cryosurgery (Almeida-Paes et al 2016), or even with a combination of low drug dosages and hyperthermia (Haruna et al 2006). The non-pharmacologic approaches are interesting because they often accelerate clinical cures, reducing treatment costs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using mouse models of experimental infection show that S. brasiliensis is highly virulent, resulting in high mortality rates in animals and a high fungal burden in several organs (Arrillaga-Moncrieff et al 2009). In humans, this species is associated with some unusual manifestations of sporotrichosis, such as hypersensitivity reactions, disseminated infection in non-AIDS patients, central nervous system tropism, and ocular involvement (Almeida-Paes et al 2014, Macedo et al 2015). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The patient showed important improvement in his clinical condition when itraconazole was replaced with a KI solution, which is quite effective for treating cutaneous sporotrichosis. 31,32 The in vitro tests revealed high MICs to itraconazole (4 μg/mL), which have also been reported by some studies 15,20,33,34 and which correlated with itraconazole treatment failure. Successful KI treatment has been reported in a highly endemic area of S. brasiliensis, 31,32,35 so KI could be an important alternative for treating itraconazole-resistant sporotrichosis due to S. globosa.…”
Section: Discussionmentioning
confidence: 56%
“…Out of all dermatosis treated with KI, most of the existing data is on sporotrichosis [13-18], and the largest study included 645 patients [32]. Nonetheless, a Cochrane review found that even in this case, there is not enough (high-quality) evidence to come to a final conclusion regarding its efficacy [33].…”
Section: Discussion/conclusionmentioning
confidence: 99%